1999
DOI: 10.1088/0031-9155/44/8/308
|View full text |Cite
|
Sign up to set email alerts
|

Dose distributions using kilovoltage x-rays and dose enhancement from iodine contrast agents

Abstract: In x-ray phototherapy of brain tumours, the tumour is loaded with iodine and exposed to kilovoltage x-rays. Due to the high photoelectric cross sections of iodine, substantial photoelectric interactions occur. The flux of photoelectrons, characteristic x-rays and Auger electrons produce a localized dose enhancement. A modified computed tomography scanner, CTRx, can be used both for tumour localization and delivery of the dose enhancement therapy. Monte Carlo methods were employed to simulate the treatment of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(74 citation statements)
references
References 14 publications
4
69
0
1
Order By: Relevance
“…6). The dose enhancement factor for iodine contrast media has previously been observed for energies near and above the K-edge of iodine (33.2 keV) (Mesa et al, 1999). Using the 90 kVp energy spectrum, the photon energy at which maximum photon yield is obtained is 31.2 keV, photon energies in the range of $ 40-50 keV contributing most prominently to the dose enhancement (Edward, 1966).…”
Section: Tl Yield Enhancement In Use Of Iodinated Contrast Mediamentioning
confidence: 93%
“…6). The dose enhancement factor for iodine contrast media has previously been observed for energies near and above the K-edge of iodine (33.2 keV) (Mesa et al, 1999). Using the 90 kVp energy spectrum, the photon energy at which maximum photon yield is obtained is 31.2 keV, photon energies in the range of $ 40-50 keV contributing most prominently to the dose enhancement (Edward, 1966).…”
Section: Tl Yield Enhancement In Use Of Iodinated Contrast Mediamentioning
confidence: 93%
“…В 1999 г. A.V. Mesa et al [51] предложили использовать ком-пьютерную томографию (КТ) для повышения дозы через фотоýлектрический ýффект. Они пре-образовали диагностический КТ в терапевтиче-ский рентгеновский аппарат и применяли йод и гадолиний как рентген-контрастные препараты.…”
Section: фотон-захватная терапияunclassified
“…9,10 This differential effect is the basis of the tighter dose distribution gradients compared with conventional radiotherapy treatments. 5,7 Synchrotron radiation X-rays produced at the ESRF (European Synchrotron Radiation Facility) medical beamline are used to perform this treatment, 11,12 since the X-ray beam is nearly parallel with high flux, which allows selecting intense tunable monochromatic beams (25 to 100 keV energy range) with a dose rate of around 1 Gy/min at 2-cm depth in water. Solberg et al 11 suggested that the use of a monoenergetic beam would result in improved dose distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Solberg et al 11 suggested that the use of a monoenergetic beam would result in improved dose distributions. Mesa et al 12 performed Monte Carlo simulations and have shown that, besides the iodine concentration, the dose distributions are heavily dependent on the external beam spectrum and could be significantly improved with optimization of this parameter. First, the optimum beam energy can be selected for radiation therapy with a compromise between maximum dose enhancement effects on the heavy element and the bone sparing effect.…”
Section: Introductionmentioning
confidence: 99%